L’estrema destra e la mobilitazione anti-gender. La famiglia, la donna-madre e l’esclusione dell’alterità nel discorso dell’AfD e di Pegida - Grippo, Andrea (Studi Politici, 2022)
The rise of the extreme right social movement and the transnational anti-gender mobilisation are among the main socio-political conflicts of the last decade. In Germany, the renewed mobilising capacity of the extreme-right has been the main platform of contestation against gender mainstreaming, so that the battle in defence of the nation and the ethnocultural connotations ascribed to its people has embraced the claim for the preservation of the traditional family and traditional gender roles. Applying the research method of frame analysis, this study aims to analyse the gender discourse of the extreme right and to highlight the ‘exclusive intersectionality’ embedded in anti-gender positions, which integrate with other frames in order to negatively define social, political and economic participation rights.